Museums 101 - Walhimer, Mark 1964- (Rowman & Littlefield, 2015)
"Looking for an A-Z, one-stop, comprehensive book on museums? Wish you were able to have one of the nation's leading museum consultants spend a couple of days with you, talking you through how to start a museum, how museums work, how to set up an exhibit, and more? If so, Museums 101 is the answer to your wishes"--Provided by publisher.